2013
DOI: 10.1134/s0006297913100015
|View full text |Cite
|
Sign up to set email alerts
|

Structure and functions of syndecans in vertebrates

Abstract: Syndecans constitute a family of transmembrane proteoglycans that perform multiple functions during development, damage repair, tumor growth, angiogenesis, and neurogenesis. Through mediating binding of a great number of extracellular ligands to their receptors, these proteoglycans trigger a cascade of reactions regulating, thereby, various processes in a cell: cytoskeleton formation, proliferation, differentiation, adhesion, and migration. In fibroblasts, syndecans are responsible for cell adhesion by modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 56 publications
0
48
0
8
Order By: Relevance
“…This is similar to the lipid raft model of mechanotransduction, where the mechanical signal is decentralized and spread throughout the cytoskeleton. The proteoglycans, Syndecans are likely candidates for transducing fluid shear stress into proliferation, differentiation, adhesion and migration [107]. The cytoplasmic domains of syndecans bind to several intracellular proteins including Src kinase and alpha-actinin, and can regulate the organization of the cytoskeleton [100].…”
Section: The Glycocalyxmentioning
confidence: 99%
“…This is similar to the lipid raft model of mechanotransduction, where the mechanical signal is decentralized and spread throughout the cytoskeleton. The proteoglycans, Syndecans are likely candidates for transducing fluid shear stress into proliferation, differentiation, adhesion and migration [107]. The cytoplasmic domains of syndecans bind to several intracellular proteins including Src kinase and alpha-actinin, and can regulate the organization of the cytoskeleton [100].…”
Section: The Glycocalyxmentioning
confidence: 99%
“…1 Evidence has suggested that aberrant vascular activation and remodeling is a key pathological feature leading to tissue fibrosis and vasculopathy characteristic of SSc. 2 Syndecans are a family of transmembrane heparan sulfate proteoglycans composed of four closely related proteins (syndecan [1][2][3][4]. Syndecans consist of the highly conserved transmembrane and cytoplasmic domains and the variable ectodomains that can be shed from the cell surface by matrix metalloproteinases and exert paracrine and autocrine effects.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly mediated by their roles as a receptor for extracellular matrix proteins and a reservoir for growth factors through binding via heparan sulfate chains. 3 Different syndecans have distinct distributions in vivo. In adult tissues, syndecan-1 is stably expressed in epithelial and plasma cells, but the detection of syndecan-1 on endothelial cells and other immune cells is seemingly difficult due to its dynamic regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Employees continue to work, forming the new relations between the conflicting goals: those that are genuine and those that are proposed by managers (Unsworth, 2014); the organizational situation remains stable or undergoes minor changes. The role of OC in achieving the commitment of personnel and organizational efficiency is also underlined by Russian researchers (Dryakhlov, 2011;Dyrin, 2006;Leonova, 2013;Morgunov, 2010;Zakharova, 2009Zakharova, , 2010Zakharova, , 2012.…”
Section: Introductionmentioning
confidence: 99%